19F MRI in orthotopic cancer model via intratracheal administration of ανβ3-targeted perfluorocarbon nanoparticles. (19th October 2018) - Xu, Xiuan; Zhang, Ruixin; Liu, Fang; Ping, Jiaqi; Wen, Xiaofei; Wang, Hongbin; Wang, Kai; Sun, Xilin; Zou, Hongyan; Shen, Baozhong; Wu, Lina
Aim: To demonstrate the feasibility of intratracheal administration in orthotopic lung cancer model with 19 F MRI.Materials & methods: αv β3 -integrin targeting ability of the perfluorocarbon (PFC) nanoparticles was tested. Orthotopic lung cancer model was established in rabbits under computed tomography guidance. αv β3 -targeted PFC nanoparticles were administrated intratracheally or intravenously, and 19 F MRI was performed before and up to 24 h after administration.Results: The targeted PFC nanoparticles could bind with αv β3 -integrin. PFC concentrations in the tumors of intratracheal group after administration were significantly higher than intravenous group.Conclusion: Intratracheal administration of PFC nanoparticles was shown to be feasible and efficacious. 19 F MRI with αv β3 -targeted PFC nanoparticles provided quantitative assessment of nanoparticles distribution and tumor angiogenesis.